2016
DOI: 10.1038/nm.4021
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial iron chelation ameliorates cigarette smoke–induced bronchitis and emphysema in mice

Abstract: Chronic obstructive pulmonary disease (COPD) is linked to both cigarette smoking and genetic determinants. We have previously identified iron-responsive element binding protein 2 (IRP2) as an important COPD susceptibility gene, with IRP2 protein increased in the lungs of individuals with COPD. Here we demonstrate that mice deficient in Irp2 were protected from cigarette smoke (CS)-induced experimental COPD. By integrating RIP-Seq, RNA-Seq, gene expression and functional enrichment clustering analysis, we ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
223
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(236 citation statements)
references
References 88 publications
7
223
4
1
Order By: Relevance
“…5C,D). We also showed that IRP2 knockout had no effect on intracellular iron content, consistent with a recent study (Cloonan et al 2016). However, IRP2 knockout reversed mitochondrial iron overload by FDXR deficiency to near normal in IRP2 −/− ;FDXR +/−/− cells, suggesting that IRP2 is an important mediator acting downstream from FDXR (Fig.…”
Section: Fdxr Regulates Iron Homeostasis and P53 Expression Through Irp2supporting
confidence: 93%
“…5C,D). We also showed that IRP2 knockout had no effect on intracellular iron content, consistent with a recent study (Cloonan et al 2016). However, IRP2 knockout reversed mitochondrial iron overload by FDXR deficiency to near normal in IRP2 −/− ;FDXR +/−/− cells, suggesting that IRP2 is an important mediator acting downstream from FDXR (Fig.…”
Section: Fdxr Regulates Iron Homeostasis and P53 Expression Through Irp2supporting
confidence: 93%
“…However, while NRF2 activation may be a common outcome of thiol-modifying compounds and Michael acceptors (36,37), any generalizable inhibition of IRP2 repression by endogenous compounds and xenobiotics is premature. Indeed, in opposition to our description of fumarate-mediated decreases in IRP2-IRE binding activity, mice exposed to cigarette smoke showed increased IRP2-IRE binding activity, and a thiophene derivative has been shown to enhance IRP2 binding to the FTL IRE (38,39). Furthermore, fumarate seems to differentially affect the translation of FTL and FTH1.…”
Section: Discussioncontrasting
confidence: 85%
“…To understand if mitochondrial iron dysregulation is a pathophysiologically relevant mechanism, deferiprone (DFP) was assessed. DFP is a clinically approved reagent that can chelate mitochondrial iron (18)(19)(20)(21). DFP effectively protected the body weight loss, preserved colon length, and reduced histological changes and pathological score in DSS-treated STEAP4 transgenic mice (Fig.…”
Section: Overexpression Of Steap4 In the Intestine Increases Mitochonmentioning
confidence: 98%